Addition of evaporated milk alters antioxdant properties of most commonly consumed coffee in Saudi Arabia - Al Doghaither, Huda A.; M. Alyousef, Manar; M. Al Selami, Nada; Al-Ghafari, Ayat B.; M. Omar, Ulfat (Penerbit Universiti Kebangsaan Malaysia, 2017)
Coffee is one of the most commonly consumed beverages worldwide. The aim of current study is to evaluate the effect of adding evaporated milk (full fat and low fat) on the antioxidant properties of coffee and to assess the possible alterations of polyphenols bioavailability when evaporated milk is added. To determine the effects of adding milk on the antioxidant activities of instant coffee, total polyphenols and flavonoids contents, 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity, hydrogen peroxide scavenging activity, ferric reducing power and ferrous ion chelating effect were determined. Total polyphenol and flavonoid contents were significantly higher (p<0.0001) in both coffee milk samples, coffee with full fat evaporated milk (CFEM) and coffee with low fat evaporated milk (CLEM), in comparison to pure coffee. Moreover, DPPH scavenging activity was significantly increased (p<0.001) in CFEM and CLEM whereas, hydrogen peroxide radical scavenging activity and ferric reducing power were significantly decreased (p<0.001) in CFEM and CLEM samples. In conclusion, our study showed that adding different concentrations of evaporated milk to instant coffee influences the bioavailability and efficacy of coffee antioxidants. This might be due to the presence of proteins and fats in milk.